Penerapan Algoritma Taboo Code Dalam Kompresi Record Pada Database - Sinaga, Ebenerzer Maston (STMIK Budi Darma, 2024)
The increasing use of information has created storage problems and indirectly increased the need to store information. Larger files require more disk space. A database record is a collection of files/tables that form a database. The problem that often occurs in database records is the large amount of data or records stored in the database, which makes the database size large. Over time the database used increases, it will quickly fill disk space. To reduce data storage space, compression techniques are used. Record compression in the database is used to reduce the size of data stored in the database. By reducing the size of records in a database, compression can save the storage space required and can affect the data transfer speed in the database. Compression of records in the database is done using an algorithm, namely the Tabo Code algorithm. The research results show that the Taboo Code algorithm can produce a good level of compression for records in the database. Compression can be measured by a high compression ratio, which means that the size of the data after compression is much smaller than the size of the original data. The results are Ratio Comprassion (RC) = 1.391, Comprassion Ratio (CR) = 71.87%, Redundancy (RD) = 28.12% and Space Saving (Ss) = 71.88%.